Services and programs to assist women in situations of violence in the municipality of Alfenas - Minas Gerais (Research, Society and Development, 2024)
Objective: To describe the services and programs in relation to the network of care for women in situations of violence in the municipality of Alfenas, MG, contextualizing the information regarding the location, telephone number, email, opening hours and technical reference present on the digital platforms and printed documents of public access belonging to the existing equipment in the municipality. Methods: This is a documentary, descriptive, exploratory research with a qualitative approach. Public domain data present on digital platforms, City Hall website and related departments. Used the snowball technique for technical visits, where one service highlights the attribution of the other. Variables considered: location, opening hours, telephone numbers, email. It does not require assessment by the research ethics committee, however it does not suggest exemption for ethical and methodological rigor. The data were tabulated in an Excel spreadsheet, analyzed qualitatively, with the help of the WebQda software, according to Bardin's content analysis technique. The results are presented in a descriptive table, with discursive exploration of the categories that emerged. Results: 28 care services for women in situations of violence were identified, distributed across the following sectors: Health, Social Action, Public Security, Judiciary, Education. Conclusion: Policies to combat violence against women are still very fragile and face several obstacles. Research that lists programs can help this information reach a greater number of people of different genders, classes, ages and needs.